Assessing the severity of fatigue crack using acoustics modulated by hysteretic vibration for a cantilever beam. (26th May 2016) - He, Qingbo; Lin, Yin
Abstract: This paper investigates fatigue crack severity assessment using acoustics modulated by hysteretic vibration for a cantilever beam. In this study, a nonlinear oscillator system is constructed to induce the hysteretic frequency response of the cantilever beam in dynamics, and the hysteretic vibration is then used to modulate the acoustic waves to generate the vibro-acoustic modulation (VAM) effect. Through modulation of hysteretic vibration, the hysteretic response of the VAM can be achieved. The experimental results further validated that the VAM hysteresis phenomenon can be enhanced with the increase of crack severity owing to the change of beam׳s effective stiffness. Simulations in the proposed physical model explained the reason of enhancement of hysteresis phenomenon. Combined with nonlinear bistable structural model, a fatigue crack severity assessment approach was proposed by evaluating the hysteretic region (e.g., bandwidth or jumping frequency) in the vibration frequency response of the VAM effect. The reported study is valuable in building a monotonic relationship to assess the severity of fatigue crack by a nonlinear acoustics approach. Highlights: Fatigue crack severity is assessed by acoustics modulated by hysteretic vibration. A nonlinear oscillator system induces hysteretic VAM effect of a cantilever beam. The VAM hysteresis phenomenon is enhanced with the increase of crack severity. Simulations validate the physical principle of enhanced hysteretic nonlinearity. The criteria of hysteretic region is more intuitive for crack severity assessment.